2011
DOI: 10.1002/jnr.22683
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 and ERK5 have distinct roles in the regulation of brain‐derived neurotrophic factor expression

Abstract: Neurotrophins play essential roles in the development, differentiation, and survival of neuronal and nonneuronal cells. Alterations in neurotrophin expression have been implicated in a variety of neurodegenerative disorders. Dysregulation of brain-derived neurotrophic factor (BDNF) has been implicated in deficits of long-term potentiation and cognition and may contribute to the development of Alzheimer's disease (AD). In this study, we used complementary pharmacological and molecular approaches to evaluate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
22
1
2
Order By: Relevance
“…To test this hypothesis further, we used a constitutively active MEK5 construct, (CA-MEK5) (Pi et al 2004), to specifically activate ERK5. We have previously reported that expression of this construct resulted in a significant increase of ERK5 phosphorylation without affecting ERK1/2 phosphorylation (Su et al 2011), demonstrating the specificity of the MEK5 mutant. Consistent with our hypothesis of a protective role of ERK5 on neuronal survival against oxidative stress, we found that transfection with CA-MEK5 led to an increase in cell survival in the face of the H 2 O 2 insult (Fig.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…To test this hypothesis further, we used a constitutively active MEK5 construct, (CA-MEK5) (Pi et al 2004), to specifically activate ERK5. We have previously reported that expression of this construct resulted in a significant increase of ERK5 phosphorylation without affecting ERK1/2 phosphorylation (Su et al 2011), demonstrating the specificity of the MEK5 mutant. Consistent with our hypothesis of a protective role of ERK5 on neuronal survival against oxidative stress, we found that transfection with CA-MEK5 led to an increase in cell survival in the face of the H 2 O 2 insult (Fig.…”
Section: Resultsmentioning
confidence: 75%
“…Given that chemical inhibitors may suffer from specificity issues and further, and comparing different pharmacological agents may be confounded by their relative efficacy against their presumptive targets (i.e., efficacy of U0126 against ERK1/2 vs. ERK5), we elected to employ an RNAi approach to selectively knock down the expression of ERK5, ERK1 or ERK2 in PC12 cells. We previously reported a successful depletion of ERK5 expression in rat primary astrocytes using this method (Su et al 2011). Indeed, transfection of siERK5 significantly inhibited NGF-or PC-induced KLF4 up-regulation, while siERK1/2 had no effect on KLF4 mRNA levels (Fig.…”
Section: Erk5 Mediates Ngf-and Pc-induced Klf4 Expressionmentioning
confidence: 79%
See 2 more Smart Citations
“…Interestingly, ERK/MAPK signaling plays a key role in the inducible expression of neurotrophins and also serves as a downstream kinase effector of neurotrophin receptor activation (Finkbeiner et al 1997;Kaplan and Miller 2000). For example, the expression of BDNF is mediated by an ERK/MAPK/CREB signaling cassette (Shieh and Ghosh 1999;Su et al 2011), and signaling via BDNF/TrkB affects cellular morphology via actuation of ERK/MAPK/CREB (Alonso et al 2004). Given these findings, one could envision MSK1 functioning within a positivefeedback circuit by which EE drives both neurotrophin expression and, in turn, neurotrophin-dependent enhancement of morphological plasticity.…”
Section: Environmental Enrichmentmentioning
confidence: 99%